2007
DOI: 10.1002/adem.200700160
|View full text |Cite
|
Sign up to set email alerts
|

Mg Based Bulk Metallic Glasses with high Mechanical Strength and Large Viscoplastic Forming Capacity

Abstract: Various Mg based BMG were successfully elaborated by copper mould casting. High strengths (> 600 MPa) were obtained in compression at room temperature associated with a large elastic strain (≈ 0.015) but also to a macroscopically brittle behavior. Deformation capacity in the glass transition interval has been investigated. For such temperatures, thanks to Newtonian rheologies, glasses exhibit a particularly good viscoplastic forming ability with low viscosities. However, in some cases, crystallization can occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…However, many questions have not been addressed: (i) What is the influence of temperature of the mechanical properties of cerium-based BMG above the room temperature? (ii) It is well known that in amorphous materials, in addition to elasticity and plasticity, a viscoelastic component exists, with a magnitude which may be very large in the supercooled liquid region [11][12][13][14][15][16][17][18][19][20][21]. What's about cerium-based materials?…”
Section: Introductionmentioning
confidence: 97%
“…However, many questions have not been addressed: (i) What is the influence of temperature of the mechanical properties of cerium-based BMG above the room temperature? (ii) It is well known that in amorphous materials, in addition to elasticity and plasticity, a viscoelastic component exists, with a magnitude which may be very large in the supercooled liquid region [11][12][13][14][15][16][17][18][19][20][21]. What's about cerium-based materials?…”
Section: Introductionmentioning
confidence: 97%
“…Plasticity induced by nanoparticle dispersion in bulk metallic glasses has been observed in Zr-and Cu-based alloys [19][20][21][22][23]. In the Mg-based BMG with gadolinium, we have shown that primary crystallization was producing large crystals of Mg 2 Cu and Cu 2 Gd (200 nm) [10,11] and that partial crystallization was reducing the stress fracture limit without any plasticity.…”
Section: Resultsmentioning
confidence: 88%
“…Therefore, a relatively round region has been assigned to demonstrate the solubility range of τ1. According to the WDS analysis of τ1 containing alloys (1)(2)(3)(4)(5)(6)(7)(8), five three-phase regions were also established: τ1 + NiY + Ni2Y3, τ1 + NiY3 + Ni2Y3, τ1 + NiY + τ5, τ1 + MgY + τ5 and τ1 + NiY3 + hcp-Y. Hara et al [7] in their hydrogen storage work on the Mg-Ni-Y system, reported an unknown phase of composition MgNiY3.…”
Section: Isothermal Section Based On Diffusion Couples and Key Samplementioning
confidence: 99%
“…The innovation and rapid development of Mg-based metallic glass can further improve the physical and chemical properties of these alloys. It has been found that amorphization to produce metallic glass by a higher cooling rate OPEN ACCESS improves the mechanical strength, hardness and corrosion resistance compared to the crystalline alloys [1][2][3][4][5]. Some of the promising metallic glasses with large super cooled liquid region have been reported in the Mg-Ni-Y system [1,6].…”
Section: Introductionmentioning
confidence: 99%